Mechanism of the Potential Therapeutic Candidate Bacillus subtilis BSXE-1601 Against Shrimp Pathogenic Vibrios and Multifunctional Metabolites Biosynthetic Capability of the Strain as Predicted by Genome Analysis - Wang, Dongdong; Li, Jiahui; Zhu, Guoliang; Zhao, Kun; Jiang, Wenwen; Li, Haidong; Wang, Wenjun; Kumar, Vikash; Dong, Shuanglin; Zhu, Weiming; Tian, Xiangli (Frontiers in Microbiology, 2020)
The global shrimp industry has suffered bacterial diseases caused mainly by Vibrio species. The typical vibriosis, acute hepatopancreatic necrosis disease (AHPND), has resulted in mass mortality and devastating economic losses. Thus, therapeutic strategies are highly needed to decrease the risk of vibriosis outbreaks. Herein, we initially identified that the growth of the causative agent of AHPND, Vibrio parahaemolyticus (VPAHPND) and other vibrios in Pacific white shrimp (Litopenaeus vannamei) was inhibited by a Bacillus subtilis strain BSXE-1601. The natural products amicoumacins A, B, and C were purified from the cell-free supernatant from the strain BSXE-1601, but only amicoumacin A was demonstrated to be responsible for this anti-Vibrio activity. Our discovery provided the first evidence that amicoumacin A was highly active against shrimp pathogens, including the representative strain VPAHPND. Furthermore, we elucidated the amicoumacin A biosynthetic gene cluster by whole genome sequencing of the B. subtilis strain BSXE-1601. In addition to amicoumacin A, the strain BSXE-1601 genome harbored other genes encoding bacillibactin, fengycin, surfactin, bacilysin, and subtilosin A, all of which have previously reported antagonistic activities against pathogenic strains. The whole-genome analysis provided unequivocal evidence in support of the huge potential of the strain BSXE-1601 to produce diverse biologically antagonistic natural products, which may facilitate further studies on the effective therapeutics for detrimental diseases in shrimp.